Distinct stages of the intestinal bacterial community of Ampullaceana balthica after salinization - Kivistik, Carmen; Käiro, Kairi; Tammert, Helen; Sokolova, Inna M.; Kisand, Veljo; Herlemann, Daniel P. R. (Frontiers in Microbiology, 2022)
Environmental disturbances influence bacterial community structure and functioning. To investigate the effect of environmental disturbance caused by changes in salinity on host protected bacterial communities, we analyzed the microbiome within the gastrointestinal tract of Ampullaceana balthica at different salinities. A. balthica is a benthic gastropod found in fresh- and mesohaline waters. Whereas the total energy reserves of A. balthica were unaffected by an increase of salinity to 3, a high mortality rate was detected after a shift from freshwater to salinity 6 suggesting a major disruption of energy homeostasis. The shift to salinity 6 also caused a change in the gastrointestinal bacterial community composition. At salinity 3, the bacterial community composition of different host individuals was related either to the freshwater or salinity 6 gastrointestinal bacterial community, indicating an ambivalent nature of salinity 3. Since salinity 3 represents the range where aquatic gastropods are able to regulate their osmolarity, this may be an important tipping-point during salinization. The change in the intestinal microbiome was uncoupled from change in the water bacterial community and unrelated to the food source microbiome. Our study shows that environmental disturbance caused by salinity acts also on the host protected microbiome. In light of the sea-level rise, our findings indicate that salinization of the near-shore freshwater bodies will cause changes in organisms’ intestinal microbiomes if a critical salinity threshold (presumably ~3) is exceeded.